A Morphologic Analysis of the Pubic Symphysis Using CT and MRI. Issue 13 (1st July 2022) - Mazura, Matej; Kachlik, David; Blankova, Alzbeta; Malikova, Hana; Whitley, Adam; Landor, Ivan; Dzupa, Valer
Abstract : Introduction: The goal of this study was to investigate prevalence and morphometric parameters of pubic ligaments and the interpubic disk and its cavity using imaging methods for use in clinical medicine. Methods: Pubic symphysis morphology was investigated in 652 patients (348 women and 304 men), from which 449 CT scans and 203 MR scans were available. The average age of men was 48 years and women 39 years. Investigated parameters included dimensions of the interpubic disk, visibility and width of the reinforcing ligaments, and visibility, dimensions, and location of the symphysial cavity. The results were compared with MR scans of 20 healthy volunteers and 21 dissected anatomic specimens. Results: The craniocaudal, ventrodorsal, and mediolateral diameters of the pubic disk were 36 to 37.7, 14.8 to 15.2, and 2.2 to 4.2 mm in women and 42 to 42.3, 18.6 to 19, and 2.4 to 4.5 mm in men, respectively. Higher age correlated with shorter mediolateral diameter and larger craniocaudal and ventrodorsal diameters. The superior pubic ligament was visible in 93.1% of men (1.44 mm thick) and in 100% of women (1.7 mm); the inferior pubic ligament in 89.7% of men (1.74 mm) and 88% of women (1.95 mm), the anterior pubic ligament in 96.6% of men (1.5 mm) and 82% of women (1.34 mm); and the posterior pubic ligament in 65.5% of men (1.18 mm) and 63.7% of women (0.83 mm). A symphysial cavity was found in 24% of men and 22.9% of women, with craniocaudal, ventrodorsal, and mediolateral dimensions of 13, 10.7, and 3.2 mm in men and 9.5, 10.7, and 3 mm in women, respectively. Conclusion: The presented morphologic parameters provide an anatomic reference for diagnostics of pathologic conditions of the pubic symphysis. The following anatomic structures should be added to the official anatomic terminology: symphysial cavity (cavitas symphysialis), retropubic eminence (eminentia retropubica), anterior pubic ligament (ligamentum pubicum anterius), and posterior pubic ligament (ligamentum pubicum posterius). Level of Evidence: II-III